Gonadotoxic effect of tramadol administration: A prospective controlled study. Issue 1 (2nd January 2022) - Soliman, Tarek; Shaher, Hussein; Mohey, Ahmed; El-Shaer, Waleed; Sebaey, Ahmed
ABSTRACT: Objective: To detect the possible gonadotoxic effects of tramadol dependence on seminal fluid parameters, and prolactin and testosterone hormone levels. Patients, Subjects, and Methods: There were 94 participants who were divided into a tramadol-dependent group (T-group; 56 patients) and a control group (C-group; 38 healthy volunteers). The following variables were evaluated: testosterone level, prolactin level, erectile function, libido, semen parameters, and effect of tramadol dose and dependence duration. Results: There was a significant increase in erectile dysfunction (ED) and decreased libido in the T-group vs C-group. Also, the serum testosterone level was lower in the T-group vs the C-group, while the serum prolactin level was significantly higher in the T-group vs the C-group. All semen parameters were low in the T-group except for abnormal forms, which were high. As the dose of tramadol increased there was a more negative effect on the previous parameter, while ED, libido, semen volume and concentration showed no significant changes. When comparing tramadol doses of 400–1000 mg/day to >1000 mg/day, the tramadol blood level increased with high doses, while serum testosterone level decreased when the dose increased and the prolactin level increased when the dose increased. Progressive motility of the sperm decreased and abnormal forms increased. Also increased duration of tramadol administration was also accompanied by a more negative effect on these parameters Conclusion: Tramadol administration has a negative effect on hormone levels, libido, erectile function, and semen characters.Abbreviations: ED: erectile dysfunction; EF: erectile function